Oral health knowledge and its correlation with the oral hygiene of University of the Philippines College of Dentistry Students S.Y. 2016-2017 - Brojan, Maria Cziara G.; Garcia, Shara Mae C. (Department of Community Dentistry, University of the Philippines Manila, 2017)
Introduction: Dental caries and periodontal diseases have always been a major public health issue here in the Philippines. This poor oral health condition in the country underscores the importance of the role of Filipino dentists in educating their patients on oral health promotion and maintenance. It is not enough to possess knowledge and verbally transmit the information. Their personal belief and practices are important because as future health providers, these will potentially influence how they motivate their patients towards improved oral hygiene. It was the aim of this study to determine if there is a correlation between oral health knowledge & oral hygiene.